Factors associated with depression and anxiety among caregivers of patients with atrial fibrillation. Issue 21 (5th December 2021) - Li, Sitong; Li, Qifan; Jiang, Chao; Chen, Xuan; Lai, Yiwei; He, Liu; Cui, Feihuan; Wu, Jiahui; Hu, Rong; Jia, Changqi; Feng, Li; Sang, Caihua; et al.
Abstract: Aims and objectives: To assess the prevalence and associated factors of depression and anxiety among caregivers of patients with atrial fibrillation. Background: Depression and anxiety are common in caregivers of patients with cardiovascular diseases, including heart failure and coronary artery disease. However, studies about depression and anxiety among caregivers of patients with atrial fibrillation are limited. Design: Cross‐sectional study. Methods: We enrolled 465 dyads of patients with atrial fibrillation and their primary family caregivers from Beijing Anzhen Hospital between September 2020 and March 2021. The patient–caregiver dyads were excluded if primary family caregivers had previous mental disorders before the patient diagnosis of atrial fibrillation. Depression and anxiety of patients and caregivers were measured by Patient Health Questionnaire‐9 and Generalized Anxiety Disorder‐7 scale. Multivariate logistic regression analysis was used to assess factors associated with depression and anxiety of caregivers. STROBE guidelines were followed to report this study. Results: The prevalence of caregiver depression (Patient Health Questionnaire‐9 score ≥5) and anxiety (Generalized Anxiety Disorder‐7 score ≥5) was 14.0% and 13.5% respectively. Caregiver number of comorbidities ≥2 and patient depression were significantly associated with caregiver depression. Caregiver age ≥65 years, caregiver female sex and patient anxiety were predictors of caregiver anxiety. Conclusions: Depression and anxiety are common in caregivers of patients with AF. Better management of caregiver mental problems and associated factors may benefit both patients and caregivers. Relevance to clinical practice: Clinicians and nurses should pay more attention to depression and anxiety in caregivers of patients with atrial fibrillation, and provide support to caregivers in most need.